Crystal structure of dithieno[2,3-d:2′,3′-d′]benzo[1,2-b:4,5-b′]dithiophene-5,10-dione, C14H4O2S4 - Jia Yan; Yu Pengling; Li Shihui; Zhao Yumei; Zheng Xiaoxin (Zeitschrift für Kristallographie - New Crystal Structures)
C14H4O2S4, monoclinic, P21/n (no. 14), a = 3.85180(10) Å, b = 8.9728(2) Å, c = 18.0073(4) Å, β = 93.554(1)°, V = 621.16(3) Å3, Z = 2, R gt(F) = 0.0411, wR ref(F 2) = 0.1091, T = 301(2) K.